2022
DOI: 10.1371/journal.pone.0261458
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and bacterial diversity of an improved anaerobic baffled reactor for the remediation of wastewater from alkaline-surfactant-polymer (ASP) flooding technology

Abstract: Alkaline-surfactant-polymer (ASP) flooding technology is used to maximize crude oil recovery. However, the extensive use of alkaline materials makes it difficult to treat the water used. Here, an improved multi-zone anaerobic baffled reactor (ABR) using FeSO4 as electron acceptor was employed to treat the wastewater from ASP flooding technology, and the effects on major pollutants (hydrolyzed polyacrylamide, petroleum substances, surfactants suspended solids) and associated parameters (chemical oxygen demand, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Table 3 shows the total number of sequencing reads available representing Operational Taxonomic Units (OTUs) in samples obtained from each reactor of the BESI ® process. The coverage rate for the samples (> 99.8%) indicated that a high proportion of the reads could be explained by the OTUs [ 31 ]. The most OTUs were found in anaerobic sludge (A1-a), which represented the inlet section of the reactor.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 3 shows the total number of sequencing reads available representing Operational Taxonomic Units (OTUs) in samples obtained from each reactor of the BESI ® process. The coverage rate for the samples (> 99.8%) indicated that a high proportion of the reads could be explained by the OTUs [ 31 ]. The most OTUs were found in anaerobic sludge (A1-a), which represented the inlet section of the reactor.…”
Section: Resultsmentioning
confidence: 99%
“…indicated that a high proportion of the reads could be explained by the OTUs [31]. The most OTUs were found in anaerobic sludge (A1-a), which represented the inlet section of the reactor.…”
Section: Microbial Community Analysismentioning
confidence: 99%
See 1 more Smart Citation